Ethnobotanical study on traditional medicinal plant species used by Raute tribe in Far-western Nepal - Madai, Janak Raj; joshi, Anand prakash; Upadhyay, Kanchan Devi (AMC Journal (Dhangadhi), 2024)
The present study has been undertaken in the Aampani & Rajaura village of Parshuram Municipality to document the indigenous knowledge of study was carried out in the Raute community. The field study involved frequent field visits to the villages, participatory observation, group discussion, and interviews with members of Raute community from March to June 2023. All together 52 plant species of medicinal properties belonging to 46 genera and 37 families were studied, among which the family Solanaceae and Cucurbitaceae is represented by the highest number of species comprising 3 species. These plant species were evaluated in terms of plant parts use category, habit category, disease use category, and mode of application to treat different ailments. All reported plant species were used for the treatment of 64 different ailments. Among these, 17 species were used to treat gastrointestinal disorders, 11 species for respiratory-related issues, 10 species for healing wounds and cut, 6 species for fever and headache, 5 species for skin-related disease and 4 for diabetes and so on. The study highlighted challenges such as easy access to modern medicine and limited recognition of traditional healers, which have contributed to declining interest among younger generations in traditional medicinal practices.